Differential susceptibility in steelhead trout populations to an emergent MD strain of infectious hematopoietic necrosis virus - Breyta, Rachel; Jones, Amelia; Kurath, Gael (Diseases of aquatic organisms, 2014)
A significant emergence of trout-adapted MD subgroup infectious hematopoietic necrosis virus (IHNV) began in the coastal region of Washington State, USA, in 2007. This emergence event lasted until 2011 and caused both asymptomatic adult fish infection and symptomatic epidemic disease and mortality in juvenile fish. Incidence of virus during this emergence demonstrated a heterogeneous distribution among rivers of the coastal region, leaving fish populations of some rivers apparently untouched while others suffered significant and recurrent infection and mortality (Breyta et. al. 2013; Dis Aquat Org 104:179-195). In this study, we examined the possible contribution of variations in susceptibility of fish populations, age-related resistance, and virus virulence to the observed landscape heterogeneity. We found that the most significant variable was host susceptibility: by controlled experimental challenge studies steelhead trout populations with no history of IHNV infection were 1 to 3 orders of magnitude more sensitive than a fish population with a long history of IHNV infection. In addition, 2 fish populations from the same river, which descended relatively recently from a common ancestral population, demonstrated 1 to 2 orders of magnitude difference in susceptibility. Fish age-related development of resistance was most evident in the more susceptible of 2 related fish populations. Finally, the strain of virus involved in the 2007 coastal Washington emergence had high virulence but was within the range of other known M group viruses tested. These results suggest that one major driver of landscape heterogeneity in the 2007 coastal Washington IHNV emergence was variation in fish population susceptibility and that this trait may have a heritable component.